Anthology of Arabic Discourse on Translation - Sara Solá Portillo (Trans)
Reseña de Anthology of Arabic Discourse on Translation Tarek Shamma y Myriam Salama-Carr (Eds.) Nueva York, Routledge, 2022, 399 pp.